The Relationship Between Law and Public Policy in Social Development - Sutrisno, Endang (Journal of Law and Social Politics, 2025)
Background: Law and public policy play a central role in social development by providing legal and institutional frameworks that regulate economic, political, and social interactions. In democratic systems, misalignment between legal frameworks and public policies often weakens governance and limits social progress. Objective: This study aims to analyze the influence of law on public policy formulation and implementation in supporting social development, identify key challenges arising from legal–policy misalignment, and propose strategies to enhance their coherence. Methods: A qualitative research approach was employed using comparative analysis of legal frameworks, policy-making processes, and selected case studies from various jurisdictions. Data were collected from legal documents, government policies, academic literature, and expert opinion. Results: The findings show that effective social development requires strong alignment between legal frameworks and public policy goals. Legal rigidity, political interference, and inconsistent enforcement are major obstacles to policy effectiveness. In contrast, integrated legal and policy mechanisms contribute to better governance, economic stability, and social welfare. Conclusion: Strengthening synergy between law and public policy through transparent legal processes, institutional reform, and inclusive policy-making can enhance social development outcomes. This study provides valuable insights for policymakers and legal scholars in improving governance and social progress.